The Influence of Usability, E-Satisfaction and E-Security on E-Loyalty of WhatsApp Mobile Instant Messaging Users - Ratna Yulis Teaningrum; Alshaf Pebrianggara; Mas Oetarjo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research examines the influence of usability, e-satisfaction, and e-security on e-loyalty in the use of the mobile instant messaging application WhatsApp. The rapid growth of information and communication technology, particularly in mobile instant messaging, has transformed how society communicates, including in Indonesia. WhatsApp, as one of the most popular applications, facilitates communication and fosters user loyalty. This study employs a quantitative approach with a descriptive method, involving a sample of 100 active WhatsApp users who have used the application for at least six months. Data was collected through questionnaires and analyzed using the Partial Least Squares (PLS) method. The findings indicate that usability and e-security have a positive and significant impact on user e-loyalty. However, e-satisfaction does not show a significant effect on e-loyalty, suggesting that while users may feel satisfied, their satisfaction does not necessarily translate into increased loyalty. This research provides valuable insights into the factors influencing WhatsApp user loyalty and underscores the need to explore additional variables that may contribute to e-loyalty.